2015
DOI: 10.1136/bmjopen-2014-007079
|View full text |Cite
|
Sign up to set email alerts
|

What is mental health? Evidence towards a new definition from a mixed methods multidisciplinary international survey

Abstract: ObjectiveLack of consensus on the definition of mental health has implications for research, policy and practice. This study aims to start an international, interdisciplinary and inclusive dialogue to answer the question: What are the core concepts of mental health?Design and participants50 people with expertise in the field of mental health from 8 countries completed an online survey. They identified the extent to which 4 current definitions were adequate and what the core concepts of mental health were. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 11 publications
4
150
0
15
Order By: Relevance
“…3 Mental health is distinct from SWB, since mental health refers to an objective state of the individual. However, there are some overlapping featuresmental health is often measured through asking people about themselves, albeit with the aim to identify their level of cognitive-emotional functioning (Manwell et al 2015). Roberts et al (2011) carried out fixed effects modelling analysis of BHPS data (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) and found that longer duration commutes were associated with worse mental health for women, but not men.…”
Section: Commuting and Mental Healthmentioning
confidence: 99%
“…3 Mental health is distinct from SWB, since mental health refers to an objective state of the individual. However, there are some overlapping featuresmental health is often measured through asking people about themselves, albeit with the aim to identify their level of cognitive-emotional functioning (Manwell et al 2015). Roberts et al (2011) carried out fixed effects modelling analysis of BHPS data (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) and found that longer duration commutes were associated with worse mental health for women, but not men.…”
Section: Commuting and Mental Healthmentioning
confidence: 99%
“…What is meant by mental health is the ability to carry out everyday activities, establish proper relationship, and exhibit proper social and cultural behavior (4). Mental health is considered as intellectual, emotional and spiritual development, positive self-perception, a sense of dignity and physical health, and interpersonal harmony (5,6).…”
Section: Contextmentioning
confidence: 99%
“…Manwell et al, promotes the formulation made by the Public Health Agency of Canada, which states that: “Mental health is the capacity of each and all of us to feel, think, and act in ways that enhance our ability to enjoy life and deal with the challenges we face. It is a positive sense of emotional and spiritual well-being that respects the importance of culture, equity, social justice, interconnections and personal dignity” [20]. …”
Section: Discussionmentioning
confidence: 99%